Study of a user-centered design approached to developing a local positioning system for smartphones - Jubaier, Ashiqur; Saha, Raj Kapoor; Tisha, Farzia Hoque (BRAC University, 2012)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2011.